Direct STR typing from fired and unfired bullet casings - Phuvadol Thanakiatkrai (2020)
© 2019 Elsevier B.V. Cartridges, bullets, and casings (CBCs) are commonly recovered after shooting incidents and could provide valuable DNA information from touch DNA that has been left behind during handling of bullets and loading of guns. Direct PCR, in which the DNA extraction and quantification steps are bypassed, has been shown to provide comparable and sometimes better results from touch DNA and trace DNA samples. Here, direct PCR was applied to touch DNA retrieved from bullet casings from three ammunition types and guns. The results were evaluated to determine whether the technique should be recommended as a standard operating protocol for forensic DNA analysts. Three experiments were carried out to investigate the following: the effect of firing bullets on DNA deposited on bullet casings; the effect of gun and ammunition types on short tandem repeat (STR) profile quality; and the feasibility of using direct PCR in real-world cases via typing of mock casework samples. DNA extraction resulted in a loss of about 40% of DNA originally deposited, and firing a bullet reduced the amount of DNA recovered by 27%. Using the direct PCR protocol, conventional extraction protocol, and dilution protocol on touch DNA from fired bullet casings, we recovered means (and 95% credible intervals), respectively, of 11.1 (7.9–13.9), 5.6 (3.0–7.7), and 2.3 (0.2–4.0) alleles. No statistical difference in alleles recovered was observed between different calibers of ammunition fired from three guns (9 mm, 7.62 mm, and 5.56 mm from Glock Model 19, AK47, and Tavor T-21, respectively). As expected, mixed DNA profiles were observed in 40% of the mock casework samples, in which guns were shared between volunteers. This study showed that direct amplification of touch DNA from bullet casings improved STR profiles. As direct PCR is quicker, cheaper, and resulted in more alleles recovered, forensic DNA analysts may benefit from using direct PCR.